Effect of processing variables on fish oil extraction - Nur Fathin Shamirah, Daud; Farhan, Mohd Said; Nur Hidayah, Mat Yasin; Aishath, Naila (Universiti Malaysia Pahang, 2025)
The accumulation of fish waste from seafood processing poses significant environmental and economic concerns. Therefore, there is a need to explore an efficient and sustainable extraction process for producing biodiesel, particularly through the extraction of fish oil rich in fatty acid methyl esters (FAME). This study investigated the effects of different processing variables, such as solvent type, temperature, and extraction time on the oil yield and FAME composition. The oil and FAME were extracted using a soxhlet extraction method. The optimal extraction conditions were ethanol, 60 °C, and 4 h, which yielded 49.0% oil yield with a high concentration of oleic acid (C18:1), ranging from 42% to 66%. These findings demonstrated that the oil extracted from fish waste has significant potential for cost-effective biodiesel production.